2006
DOI: 10.2172/889071
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Enhanced Attenuation of Chlorinated Solvents Using RT3D

Abstract: This document was printed on recycled paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Reaction parameters may be defined as spatially constant or spatially variable, depending on site conditions and the available information. For instance, if multiple geochemical settings (as discussed in Johnson et al [2006]) are identified within the model domain, the parameters in one area can be set to different values than for another area. Reaction parameter values can vary spatially because of differences in geochemistry (e.g., concentrations/types of electron acceptors, anaerobic/anoxic/aerobic setting), temperature, substrate availability, and microbial population (in terms of both numbers of bacteria and types of bacteria).…”
Section: Sum Of Yields Equals 100%mentioning
confidence: 99%
See 2 more Smart Citations
“…Reaction parameters may be defined as spatially constant or spatially variable, depending on site conditions and the available information. For instance, if multiple geochemical settings (as discussed in Johnson et al [2006]) are identified within the model domain, the parameters in one area can be set to different values than for another area. Reaction parameter values can vary spatially because of differences in geochemistry (e.g., concentrations/types of electron acceptors, anaerobic/anoxic/aerobic setting), temperature, substrate availability, and microbial population (in terms of both numbers of bacteria and types of bacteria).…”
Section: Sum Of Yields Equals 100%mentioning
confidence: 99%
“…RT3D is a numerical code for simulating three-dimensional multi-species reactive transport in groundwater for a user-configured site model [Clement, 1997;Clement et al, 1998;Clement and Johnson, 2002;Johnson et al, 2006]. RT3D can provide information to help analyze the relative importance of different fate and transport processes at an individual site and assess the plume in terms of a mass balance approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-specific knowledge from field data or laboratory tests should be applied to determine an appropriate model configuration for reaction parameters (i.e., the values and the spatial distribution). RT3D is a numerical code for simulating three-dimensional multi-species reactive transport in groundwater Johnson et al, 2006a]. RT3D can provide information to help analyze the relative importance of different fate and transport processes at an individual site and assess the plume in terms of a mass balance approach.…”
Section: Required Inputmentioning
confidence: 99%
“…The user is assumed to be familiar with both MODFLOW and RT3D Johnson et al, 2006a] as well as the process of defining a model, running the numerical codes, and accessing the resultant output. While MODFLOW and RT3D models are often configured and run from within a third party graphical user interface such as GMS , Visual Modflow , PMWIN , or Groundwater Vistas , the rtFlux software runs external to these groundwater modelling software packages.…”
Section: Using the Rtflux Utilitymentioning
confidence: 99%